The State of Agile Leadership Research: A Bibliometric Exploration of Academic Contributions - Helina Apriyani; Aan Komariah; Asep Suryana; Nur Aedi (Universitas Negeri Malang, 2025)
This study explores the state of agile leadership research through a bibliometric analysis of academic contributions, focusing on publication trends, geographic distribution, and thematic insights. Using the Scopus database and the keyword “agile leader*,” 70 publications from 2010 to 2024 were identified. Analysis tools VOSviewer and Biblioshiny were employed to visualize co-occurrence networks and identify key research themes. Results show a significant increase in publications starting in 2020, reflecting heightened interest driven by contemporary challenges and digital transformation. Indonesia, Turkey, and India emerged as leading contributors. Thematic analysis revealed clusters related to organizational agility, digital transformation, crisis management, and leadership style. This study underscores the multidimensional nature of agile leadership and highlights its relevance across industries and global contexts. Future research should explore the application of agile leadership principles within the education sector to foster adaptable, innovative, and resilient educational institutions.